Periodontal approach in the management of alveolar cleft - Vinathi Reddy Kankara; Sahithi Annavarapu; Krishnanjeya Reddy Pathakota; Preethi Krishnan (Wolters Kluwer Medknow Publications, 2020)
The alveolar cleft is a bone-related developmental defect in the alveolar process of the maxillae, which is termed as cleft alveolus. The deformity occurs in 75% of the cleft palate and lip patients. Reconstructive surgery can provide both functional and esthetic benefits to such individuals. Conflicting opinions exist on the management of alveolar cleft, and these affect the treatment planning. We present the case of a 19-year-old female patient with a complaint of mobile teeth in the left frontal region of the upper jaw. On clinical examination, unilateral cleft alveolus was observed between the left lateral incisor and the canine region. A multidisciplinary approach was adopted, orthodontic treatment was started, and periodontal regenerative surgery was planned. This report also discusses the substitution of autogenous bone grafts with other materials such as allogenic grafts (demineralized freeze-dried bone allograft), platelet-rich plasma, platelet-rich fibrin membranes, and amnion membranes, which could serve as a new line of treatment for the condition.